Aesthetic Engagement: Anna Zanoli's Cultural Programmes for the RAI (1968–1974). (1st October 2016) - Seger, Monica
Abstract : This essay examines a series of television programmes produced by Anna Zanoli for the RAI during the years 1968 to 1974. Each episode of the programmes in question is hosted by a notable cultural figure and dedicated to the promotion of a 'forgotten' work of Italian art, architectural monument or landscape. The essay argues that by exploring Italy's rich visual-cultural patrimony through the use of a new popular media, Zanoli's programmes seek to redefine Italian culture as simultaneously high and low. Furthermore, by featuring well-known hosts from the worlds of cinema, literature, and politics, the programmes engage with the question of impegno as they propose an ethical commitment to aesthetic appreciation.